Biological determination of gender socialization - Redžić, Saduša F. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The author raises the question whether the differences in gender socialization of girls and boys are conditioned by sexual facts, and in what way. Moreover, she asks whether there are differences in the process that are the result of inherent characteristics of male and female beings: whether, in addition to social, there are biological detrminantes that would give a different product of gender socialization of girls and boys? Looking for answers she examines the scientific facts and elements of theories that could go in favor of this thesis, as well as possible social conditionality of these facts. Gender socialization is determined by child’s sex, but not by biological characteristics, but by gender as a category which builds a sex and gender identity: there is a variety of social settings according to the given sex characteristics of a boy or a girl and different meanings that society ascribes to them.